2015
DOI: 10.1155/2015/184616
|View full text |Cite
|
Sign up to set email alerts
|

Modification Effect of Cellulase on the Physicochemical Characteristic of Polysaccharides Edible Films

Abstract: This study was conducted to assess hydrolytic influence of cellulase (C) on the physicochemical stability of chitosan (CH)/hydroxypropyl methylcellulose (HPMC) films in time of storage (T). Initially, nine films were physically characterized by contact angle, water vapour permeability (WVP), water activity(aw), tensile test, dynamic mechanical thermal analysis (DMTA), and thermogravimetric analysis (TGA) and chemically by Fourier Transform Infrared Spectrometry (FTIR). The contact angle results varied from 53.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…To the best of our knowledge, the usage of a hydrolytic enzyme (except lysozyme) as an additive in polysaccharide meat coatings for improving its antimicrobial activity is novel. Our FT-IR analysis confirmed the hydrolysis of chitosan by cellulase and showed that the physicochemical properties of such films were comparable to that reported by a previous study [ 10 ]. The objective of this study was to optimize the composition of edible food coatings based on hydroxypropyl methylcellulose, chitosan, and cellulase, and to improve the shelf-life and quality of pork meat.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…To the best of our knowledge, the usage of a hydrolytic enzyme (except lysozyme) as an additive in polysaccharide meat coatings for improving its antimicrobial activity is novel. Our FT-IR analysis confirmed the hydrolysis of chitosan by cellulase and showed that the physicochemical properties of such films were comparable to that reported by a previous study [ 10 ]. The objective of this study was to optimize the composition of edible food coatings based on hydroxypropyl methylcellulose, chitosan, and cellulase, and to improve the shelf-life and quality of pork meat.…”
Section: Introductionsupporting
confidence: 90%
“…It exerts a particularly potent inhibitory effect against bacteria [ 14 ]. Cellulase has been shown to hydrolyse chitosan resulting in the production of chitooligomers [ 10 ]. Available evidence suggests that chitooligomers may have better antimicrobial properties than chitosan [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…UV irradiation can alter the contact angle and surface properties of biopolymeric films, leading to changes in surface roughness and polarity [53]. Furthermore, Zimoch-Korzycka et al [54] reported that the presence of enzymes such as cellulase in polysaccharide films can impact their physicochemical stability over time, affecting parameters such as water vapor permeability and tensile strength. Xu et al [53] found that UV irradiation exposure decreases water contact angles in certain polymer films, attributed to the formation and release of surfactants from irradiated surfaces.…”
Section: Contact Angle Before and After Ultraviolet Radiationmentioning
confidence: 99%
“…Lopes, Martins, Fonseca, and Vicente (2011) also noticed that WVP of chitosan films were not affected by the enzyme, glucose oxidase incorporation [44]. Cellulase did not change water resistance of chitosan-hydroxypropyl methylcellulose films [10]. However, interactional effect of C/L and CH blend as well as chitosan influence was significant.…”
Section: Water Vapour Permeabilitymentioning
confidence: 99%
“…These include polysaccharides: chitosan [1], cellulose [2], starch [3], and carrageenan [4], proteins: gelatin [5], collagen [6], and lipids [7]. Enzymes are also used to improve or change features of polymers: transglutaminase [8], lysozyme [9], or cellulase [10].…”
Section: Introductionmentioning
confidence: 99%